(untitled) (Mediscope, 2023)
Background: Peptic ulcer diseases (PUD) are common conditions reported in daily clinical practice. Proton pump inhibitors (PPIs) are the most potent pharmacological inhibitors of gastric acid secretion. Aims & objectives: This study aimed to evaluate & understand the clinical presentation and management of PUD with PPIs in general practice. Methods: This prospective study was conducted on 150 diagnosed cases of PUD patients in a single center of private practice in rural areas from February 2022 to August 2022. Patients were enrolled by following inclusion & exclusion criteria with informed written consent. Eight (08) weeks after the completion of treatment by giving PPIs, a repeat endoscopy was done to see the improvement of healing of the ulcer. All data were collated and results were expressed in percentages which are illustrated in different tables & figures. Results: Among 150 endoscopically diagnosed PUD patients major age group was 31-40 years (50%) of both sexes where the male (58.66%) were more predominant. Abdominal pain (82%), heartburn (56.66%), etc were the main clinical symptoms of the patients who were referred for endoscopy. After confirming the diagnosis, PPIs were given to the patients. Esomeprazole (34.66%), lansoprazole (22%), pantoprazole (18.66%), etc were prescribed frequently. After 8 weeks of treatment, repeat endoscopy revealed that the ulcer was completely healed in 65.33% of patients whereas only 6.66% had no improvement. Conclusion: The majority of the patient are almost cured of PUD by receiving various types of PPIs which are very effective drugs for healing peptic ulcer disease. Mediscope 2023;10(1): 22-30